2000
DOI: 10.1088/0305-4470/33/45/307
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical quantum optics

Abstract: A new scheme of field quantization is proposed. Instead of associating with different frequencies different oscillators we begin with a single oscillator that can exist in a (quantum) superposition of different frequencies. The idea is applied to the electromagnetic radiation field and nonrelativistic quantum optics. Employing a Dirac-type mode-quantization of the electromagnetic field and using a single oscillator we obtain several standard properties such as coherent states or spontaneous and stimulated emis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…This is a consequence of the fact that the cases k = 0 and k = 0, k 2 = 0, correspond to representations of the Poincaré group induced from SL(2, C) and E(2), respectively. It is quite remarkable that the ultraviolet cut-offs discussed in [1] appeared automatically due to the same property of the formalism: The nontrivial structure of the vacuum state. In the case of ultraviolet and vacuum divergences the regularization is a consequence of square integrability of O(k).…”
Section: Radiation Fields Via S Matrix In Reducible Representationmentioning
confidence: 96%
See 1 more Smart Citation
“…This is a consequence of the fact that the cases k = 0 and k = 0, k 2 = 0, correspond to representations of the Poincaré group induced from SL(2, C) and E(2), respectively. It is quite remarkable that the ultraviolet cut-offs discussed in [1] appeared automatically due to the same property of the formalism: The nontrivial structure of the vacuum state. In the case of ultraviolet and vacuum divergences the regularization is a consequence of square integrability of O(k).…”
Section: Radiation Fields Via S Matrix In Reducible Representationmentioning
confidence: 96%
“…The idea of reducible quantization is to take a(k, s) as an operator analogous to the operator one finds for a harmonic oscillator whose frequency is indefinite. In the nonrelativistic case there is only one parameter ω and one finds [1] the reducible representation of CCR a(ω) = |ω ω| ⊗ a where a comes from the irreducible representation [a, a † ] = 1 [5]. The electromagnetic field involves the 3-momentum k and two polarizations.…”
Section: Reducible Quantizationmentioning
confidence: 99%
“…Recently, in [1], it was shown that the representation can be, in principle, directly tested in cavity QED. The N -representation of electromagnetic field operators was introduced in [10], and further analyzed and generalized in [11,12,13,14].…”
Section: N -Representation Calculationmentioning
confidence: 99%
“…Such a Hilbert space represents essentially a single harmonic oscillator of indefinite frequency (for physical motivation cf. [23,24] and the Appendix in [15]). An important property of the representation is that k I k = I is the identity operator in H. A vacuum of this representation is given by any state annihilated by all a k .…”
Section: N < ∞ Representationmentioning
confidence: 99%